2012
DOI: 10.2478/v10046-012-0013-0
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers and Their Potential Use in Transplantation

Abstract: The article presents an overview of literature related to two topical issues in modern medicine: transplantation and biomarkers. There have been advances made in the use of immunoenzymometric and immunoadsorption assays in organ transplantation clinics for evaluating different situations. However, these methods fail to solve more complex and ambiguous transplantation problems: tolerance, personification of treatment, etc. In this regard, the first results of prospective studies using OMICS methods of genomics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 50 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…14 rejection, treatment outcomes, and immunosuppressive therapy adaptation. 19,20 Table 2 is a summary of omics studies published in the transplantation field with >70 reported articles. These studies focused on acute rejection (AR) with very little progress on chronic rejection/loss.…”
Section: Phenomicsmentioning
confidence: 99%
See 1 more Smart Citation
“…14 rejection, treatment outcomes, and immunosuppressive therapy adaptation. 19,20 Table 2 is a summary of omics studies published in the transplantation field with >70 reported articles. These studies focused on acute rejection (AR) with very little progress on chronic rejection/loss.…”
Section: Phenomicsmentioning
confidence: 99%
“…Monitoring biomarkers in transplantation aims to predict rejection, treatment outcomes, and immunosuppressive therapy adaptation. 19,20…”
Section: Omics Studies In Transplantationmentioning
confidence: 99%